Household Waste Management in Cameroon: The Case of Bamenda and Buea Municipalities - Forje, Lema Catherine (Advances in Social Sciences Research Journal, 2021)
Urban sanitation and hazard risk reduction strategies that aim to maintain a clean and healthy society will only be successful and sustainable if it includes educating and training the people on how to handle their household waste. Nations and organisations must innovate in order to sustain the health of population growth and other global demands. It is not easy to obtain a complete assessment of risk involve in any undertaking. The problem is even more in an innovative project like the case of hysacam waste disposal in Buea and Bamenda in Cameroon. What distinguishes standard processes from innovation is their level of uncertainty. Therefore, ways of assessing and addressing the magnitude of risks involve must come high on the list of techniques for managing innovations. The risk surrounding garbage disposal in Cameroon is a course for concern. The objective of this paper is to present and discuss the assumptions which underlie the key frame of reference used to understand waste disposal in order to make garbage disposal using the new system risk free and sustainable. The study focuses on household’s waste disposal in Bamenda and Buea towns in Cameroon. According to prior studies in this area, (Jake Ansell & Frank Wharton 1992; Keith Goffin & Rick Mitchell 2005) risk is an unavoidable feature of human existence. Neither man nor organisations/societies can survive for long without taking risks. Mark and Eve (2006) suggest that people be advised to separate organic waste from solid waste before depositing for collection to a compositing depot. Data was gathered through face to face interview with those disposing garbage and the population concern. In all, 150 people were interviewed, 5 employees holding executive posts, 35 workers involve in the day to day carrying of garbage, 100 service users in the town of Buea and Bamenda where the service is being delivered and 10 people, both service delivers and service users in Douala (Cameroon) where such a service started and has since been operating for long (since the 1960s) were interviewed. Data is analysed both qualitative and quantitative. Result suggests that while the innovative garbage disposal technique is good as it is quick and cover large areas, keeps the city clean for healthy living, it is an innovative action therefore, both the service providers and users need to be trained (educated) to make the service worthwhile and sustainable. Education will empower people with appropriate knowledge on how to handle garbage with care. The implications would be: reduced risk of bacterial spread in streets, reduced ardour, clean air and quality well being greatly improved. The validity of the study lies in its ability to spread information that can improve the operation system of garbage disposal, making the service attain its objective of keeping a city clean and promote healthy living.